2007
DOI: 10.1111/j.1475-6773.2007.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Staffing Levels: Impact of Organizational Characteristics and Registered Nurse Supply

Abstract: This study is the first to show that hospital RN staffing levels on both intensive care and nonintensive care units decrease as the supply of RNs in the surrounding geographic area decreases. We also show that LPN hours rise in areas where RN supply is lower. Further research to describe the quality of hospital care in relation to the supply of nurses in the area is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
1
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 29 publications
3
28
1
7
Order By: Relevance
“…Four of six studies found that higher nurse staffing levels were significantly associated with shorter length of hospital stay or reduced rates of extended hospital stays (Blegen et al, 2008, Frith et al, 2010, Spetz et al, 2013). …”
Section: Other Outcomesmentioning
confidence: 99%
“…Four of six studies found that higher nurse staffing levels were significantly associated with shorter length of hospital stay or reduced rates of extended hospital stays (Blegen et al, 2008, Frith et al, 2010, Spetz et al, 2013). …”
Section: Other Outcomesmentioning
confidence: 99%
“…Market-level workforce characteristics could affect the regional supply of nursing staff (Blegen, Vaughn, and Vojir 2008), which in turn could affect nursing costs. We defined market area as the health service area (HSA) or the primary metropolitan statistical area (PMSA) in which a VAMC was located.…”
Section: Variable Definitionmentioning
confidence: 99%
“…www.kan.or.kr (Bhaskar, Manning, & To, 2002;Greene & Nordhaus-Bike, 1998;Yett, 1966) 선행 연구 결과에 의하면 노동시장의 구조적 특성 이외에도 병원조 직의 특성 (Blegen, Vaughn, & Vojir, 2008;Kim, June, & Cho, 2005;Mullner, Beyers, Levy, Byre, & Mallin, 1983;, 환자의 특성 (Blegen, Goode, & Reed, 1998;Brewer & Frazier, 1998;Hodge et al, 2004), 지역 특성 등의 다양한 요 인들이 간호사 수요에 영향을 미치는 것으로 보고되고 있다 (Bloom, Alexander, & Nuchols, 1997;Grumbach et al, 2001;Robinson, 1988;Seago et al). 따라서 본 연구에서는 지역별 간호사 노동시장의 구조 적 특성을 분석하고 이를 통해 도출된 노동시장 특성 변수들이 병 원의 간호사 확보수준에 미치는 영향을 파악하였다.…”
unclassified
“…(Miller, 1982). (Blegen et al, 2008;Kim et al, 2005;Mullner et al, 1983;Seago et al, 2001). 또한 병원에 입원하는 환자의 특성으로 급성기 환자들 이 많을수록 또는 환자 중증도가 높아질수록 간호사 확보수준이 더 많은 것으로 보고하고 있다 (Blegen et al, 1998;Blegen et al, 2008;Brewer & Frazier, 1998;Hodge et al, 2004;Seago et al).…”
unclassified
See 1 more Smart Citation